A new eight-cation inverse high entropy spinel with large configurational entropy in both tetrahedral and octahedral sites: Synthesis and cation distribution by X-ray absorption spectroscopy. (November 2020) - Fracchia, Martina; Manzoli, Maela; Anselmi-Tamburini, Umberto; Ghigna, Paolo
Abstract: In this work we report the synthesis of (Co, Mg, Mn, Ni, Zn)(Al, Co, Cr, Fe, Mn)2 O4 in a single-phase spinel structure (space group F d 3 ¯ m). The chemical homogeneity and purity of the sample were checked through X-ray diffraction, high resolution transmission electron microscopy and energy dispersive X-ray spectroscopy. The analysis of the pre-edge peaks of the X-ray absorption spectra for all the transition metals clearly indicated the presence of a partial degree of inversion in the spinel structure. This material is characterized by a particularly large configurational entropy, regarding both the A and the B sites, leading to a total value equal to 3.3 in R unit. Graphical abstract: Image, graphical abstract